Design and experimental validation of sliding knife notch-type disc opener for a no-till combine harvester cum seed drill - Qin, Kuan; Ding, Weimin; Ahmad, Fiaz; Fang, Zhichao (International Journal of Agricultural and Biological Engineering, 2018)
One major constraint in developing a combine harvester cum seed drill (CHCSD) is the limited space available for the attachment of no-till furrow openers. Investigating the straw stubble cutting and furrow opening performance of small-sized disc furrow openers is critically important for the development and the optimization of the no-till seeding assemblies. A set of down-scaled sliding knife notch-type disc opener (SKO), modified notch-type disc opener (MNO) and smooth-type disc opener (SDO), with upper size limit of 160 mm, were designed and fabricated for field testing. Experimental results show that for small-sized disc furrow openers of the same type, a larger disc diameter yields a greater furrow depth and width. For small-sized disc furrow openers with an identical diameter, SKOs yield a greater furrow depth and width than MNOs, with SDOs yielding the lowest values. The measured furrow depth and width for an SKO with diameter of 160 mm are 3.52 cm and 3.56 cm, respectively, meeting the no-tillage furrowing requirements for a CHCSD. The highest stubble cover rate of 62.5% is obtained for the SKO with diameter of 160 mm. Therefore, this opener has greater ability to remove stubble from the furrow and seeding band than the other designs. Finally, experimental results of the stubble cutting rates confirm that, for irregularly placed straw and residue, the stubble cutting rate of the SKO with diameter of 160 mm is the highest at 61.7%. Keywords: no-tillage, small-sized, disc furrow opener, furrow type, stubble removal DOI: 10.25165/j.ijabe.20181104.3498 Citation: Qin K, Ding W M, Ahmad F, Fang Z C. Design and experimental validation of sliding knife notch-type disc opener for a no-till combine harvester cum seed drill. Int J Agric & Biol Eng, 2018; 11(4): 96–103.